Investigations of Physical and Rheological Properties of Aged Rubberised Bitumen - Asim Hassan Ali; Nuha S. Mashaan; Mohamed Rehan Karim (Advances in Materials Science and Engineering)
Several road pavement distresses are related to rheological bitumen properties. Rutting and fatigue cracking are the major distresses that lead to permanent failures in pavement construction. Influence of crumb rubber modifier (CRM) on rheological properties of bitumen binder such as improvement of high and intermediate temperatures is investigated in the binder’s fatigue and rutting resistance through physical-rheological changes in this research. The bitumen binders were aged by rolling thin film oven (RTFOT) to simulate short-term aging and pressure aging vessel (PAV) to simulate long-term aging. The effects of aging on the rheological and physical properties of bitumen binders were studied conducting dynamic shear rheometer test (DSR), Brookfield viscometer test, softening point test, and penetration test. The results showed that the use of rubberised bitumen binder reduces the aging effect on physical and rheological properties of the bitumen binder as illustrated through lower aging index of viscosity, lower aging index of , and an increase in with crumb rubber modifier content increasing, indicating that the crumb rubber might improve the aging resistance of rubberised bitumen binder. In addition, the results showed that the softening point increment () and penetration aging ratio (PAR) of the rubberised bitumen binder decreased significantly due to crumb rubber modification. Furthermore, the higher crumb rubber content, the lower after PAV aging, which led to higher resistance to fatigue cracking bitumen.